2001
DOI: 10.1089/10507250152741028
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of [18F]-Fluorodeoxyglucose-Avid Metastatic Thyroid Cancer Lesions to Treatment with High-Dose Radioactive Iodine

Abstract: Radioactive iodine (131I) is an important therapeutic option for the treatment of metastatic thyroid carcinoma. Survival in patients with metastases that concentrate radioiodine is better than those whose metastatic lesions do not take up radioiodine. Survival is markedly reduced in patients who have metastatic lesions that concentrate 18F-fluorodeoxyglucose (FDG) on positron emission tomography (PET). In this retrospective study, we evaluated the ability of 131I to destroy FDG-avid metastatic lesions in thyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 165 publications
(87 citation statements)
references
References 18 publications
1
83
1
2
Order By: Relevance
“…Although not specifically limited to pulmonary lesions, patients with increasing volumes of 18-fluorodeoxyglucose (FDG)-avid disease seen on positron-emission tomograpy (PET) scans were less likely to respond to radioiodine and more likely to die during a 3-year follow-up compared with FDG-negative patients (257). One study found that radioiodine therapy of metastatic lesions that were positive on FDG-PET scanning was of no benefit (258). In other studies of FDG-PET imaging, however, insufficient details exist in patients known to have pulmonary metastases to assess the utility of this modality to predict treatment response or prognosis (259).…”
Section: What Is the Most Appropriate Management Of Patients With Metmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not specifically limited to pulmonary lesions, patients with increasing volumes of 18-fluorodeoxyglucose (FDG)-avid disease seen on positron-emission tomograpy (PET) scans were less likely to respond to radioiodine and more likely to die during a 3-year follow-up compared with FDG-negative patients (257). One study found that radioiodine therapy of metastatic lesions that were positive on FDG-PET scanning was of no benefit (258). In other studies of FDG-PET imaging, however, insufficient details exist in patients known to have pulmonary metastases to assess the utility of this modality to predict treatment response or prognosis (259).…”
Section: What Is the Most Appropriate Management Of Patients With Metmentioning
confidence: 99%
“…This approach may identify the location of persistent disease in approximately 50% of patients (203,280) with a wide range of reported success. Some investigators have reported a decrease in serum thyroglobulin after empiric radioiodine therapy in patients with negative RxWBS (281,282), but there is no evidence for improved survival with empiric therapy in this setting (258,283). On the other hand, serum thyroglobulin levels may decline without specific therapy (282).…”
Section: How Should Thyroglobulin-positive Patients Be Managed?mentioning
confidence: 99%
“…8 This change in biologic behavior has been attributed to the presence of poorly differentiated elements in the metastatic tumor of these patients. 9 However, to our knowledge, no study to date has been performed to examine the histology of FDG-PET-positive, RAI-refractory (RAIR) metastatic thyroid carcinomas.…”
mentioning
confidence: 99%
“…Even high-dose I-131 therapy is quite ineffective in treating FDG-positive metastatic thyroid cancers. Therefore, in patients with Tg-positive and I-131-negative tumors, the complete surgical removal of iodine-negative lesions is the only curative treatment option (12).…”
Section: Discussionmentioning
confidence: 99%